PENGARUH LITERASI KEUANGAN DAN SELF CONTROL TERHADAP PENGELOLAAN KEUANGAN PRIBADI MAHASISWA UNIVERSITAS PGRI SEMARANG - Mandariska Dara Aprillia; Syifa Tiara Ramadhina; Rauly Sijabat (Jurnal Ekonomi dan Bisnis, 2024)
The lack of knowledge about financial management causes students to be less responsible for managing their own finances. find out the influence of students' financial literacy skills and self-control on students' personal financial management so that they can control students' personal finances more eflectively and efficiently according to their needs. This research is a type of quantitative research. Arikunto (2006) explains that quantitative research is a research method that prioritizes the use of data in the form of numbers, starting from the data collection process, interpreting the results, to presenting the findings. Meanwhile, according to Creswell (2012), quantitative research requires an explanation from the researcher about the influence of each variable on other variables. Financial Literacy has a significant eflect on Personal Financial Management. Self Control has a significant eflect on Student Personal Financial Management. Financial Literacy and Self Control have a significant eflect on Student Personal Financial Management. Financial literacy has a significant eflect on students' personal financial management at PGRI University Semarang. A high level of financial literacy will improve students' personal financial management. Financial Literacy and Self Control also significantly influence students' personal financial management, with good financial literacy and good self control contributing to better management of students' personal finances.